2020
DOI: 10.1097/sih.0000000000000402
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Stress Indicators of Heart Rate Variability and Electrodermal Activity With Application in Healthcare Simulation Research

Abstract: Summary Statement Psychological stress arises from a stressor placed on an individual that leads to both emotional and physiological responses. The latter is referred to as psychophysiological stress. Healthcare simulation provides a platform to investigate stress psychobiology and its effects on learning and performance. However, psychophysiological stress measures may be underused in healthcare simulation research. The inclusion of such measures with subjective measures of stress in healthcare simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…10 LF and HF spectral, and the derived LF/HF ratio, were also found to be descriptive for parasympathetic and sympathetic states. 11 In this study, we found a significant correlation between both mean heart rate and SI as well as SI and RMSSD. However, we were not able to demonstrate significant changes for LF/HF ratio.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…10 LF and HF spectral, and the derived LF/HF ratio, were also found to be descriptive for parasympathetic and sympathetic states. 11 In this study, we found a significant correlation between both mean heart rate and SI as well as SI and RMSSD. However, we were not able to demonstrate significant changes for LF/HF ratio.…”
Section: Discussionsupporting
confidence: 55%
“…10 Low-frequency (LF) and high-frequency (HF) spectral analysis and the LF/HF ratio were also calculated. 11…”
Section: Methodsmentioning
confidence: 99%
“…Various physiological parameters can be captured, such as electrodermal activity (EDA), electrocardiogram (ECG), blood oxygen levels, or lung capacity. This information could be useful to detect and evaluate the stress of the subjects (e.g., the rescuers) wearing the sensors [ 49 , 50 , 51 ].…”
Section: Implementation Of X-ioca For Sar Missions: Sar-iocamentioning
confidence: 99%
“…For example, if one looks at the VR adaptations of the Trier Social Stress Test mentioned in Section 4.1.4, one finds that in all the listed examples the heart activity is measured. Two other signals frequently used in research to indicate changes in stress level is EDA (Kurniawan et al, 2013;Anusha et al, 2017;Bhoja et al, 2020) and skin temperature (Vinkers et al, 2013;Herborn et al, 2015). Both signals and heart rate variability were compared by Cho et al (2017) in VR.…”
Section: Stressmentioning
confidence: 99%